Photography after photography gender, genre, history - Godeau, Abigail Solomon (Duke University Press Books, 2017)
Presenting two decades of work by Abigail Solomon-Godeau, Photography after Photography is an inquiry into the circuits of power that shape photographic practice, criticism, and historiography. As the boundaries that separate photography from other forms of artistic production are increasingly fluid, Solomon-Godeau, a pioneering feminist and politically engaged critic, argues that the relationships between photography, culture, gender, and power demand renewed attention. In her analyses of the photographic production of Cindy Sherman, Robert Mapplethorpe, Susan Meiselas, Francesca Woodman, and others, Solomon-Godeau refigures the disciplinary object of photography by considering these practices through an examination of the determinations of genre and gender as these shape the relations between photographers, their images, and their viewers. Among her subjects are the 2006 Abu Ghraib prison photographs and the Cold War-era exhibition The Family of Man, insofar as these illustrate photography's embeddedness in social relations, viewing relations, and ideological formations.